Homens em análise : destinos do falo e travessias da virilidade na psicanálise lacaniana - Vinícius Moreira Lima (2022)
In this work, written upon the background of an interface between Lacanian psychoanalysis and contemporary knowledge about gender, race and sexuality, we seek to discuss some of the destinations that an analytical experience can offer to the phallus and virility through the study of clinical cases and the testimonies of the pass of men who went through this experience. As a starting point, we formulate the notion of a comic virility, that is, a specific way of embodying masculinity guided by a virile ostentation that denies its own castration and refuses femininity, making a semblance of the possession of the phallus while the subject, deep down, knows he doesn't have it. Seeking to locate the subjective coordinates that underlie the position of the “male”, we investigate the place of the degradation of the object in the love life of men, as well as the (non-)relationship between the phallus and the penis, which we propose to name here as an indexed disagreement. Along the way, we use passages from Freudian cases reread by Lacan – Little Hans, the Rat Man, the Wolf Man – as well as clinical cases produced by Lacanian literature – Ella Sharpe's patient, Lacan's impotent patient, the testimonies of the pass by Jésus Santiago and Bernardino Horne, among others – in order to gather elements that allow us to think about masculinities in the psychoanalytic clinic. Finally, we investigate Jacques-Alain Miller's formulation according to which virility has a fantasy structure, linking the construction of fantasy to the logic of sexuation. As a result, guided by two conceptions of the end of analysis provided by the work of Jacques Lacan (the disidentification to the phallus and the traversal of the fantasy), we were able to place some of the effects of an analysis on the experience of masculinity in the following way. From the perspective of disidentification to the phallus, the course of an analysis would allow a subject to mourn being the phallus that completes the Other, consenting to the bar that marks the incompleteness - or even the non-existence - of this Other and authorizing himself to assume the potholed dimension of desire, without having to subscribe to the imperatives of virility or to the scripts of cis-heteronormativity. From the perspective of the traversal of the fantasy, the operation of an analysis would lead a speaking being to access the way in which he interpreted his place as an object before the Other and the way in which he responded to this in his endeavor to become a subject, opening up a process of desubjectivation through the emptying of the object's imaginary consistency. In doing so, an analysis would allow an analysant to stop aspiring to virility and to be able to say yes to femininity, that is, to authorize himself of the feminine that traverses him in its own way. In this sense, the traversal of the fantasy can be considered as an operation that dismantles the virile decoy, since, through this traversing, a subject is led to recognize the structure of semblance of virility itself, giving him the possibility to consent to castration and, eventually, to access an Other jouissance beyond the phallus, by allowing himself to be traversed by something of the hole.